2014
DOI: 10.3389/fneur.2014.00238
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Dysregulation, Gene Networks, and Risk for Schizophrenia in 22q11.2 Deletion Syndrome

Abstract: The role of microRNAs (miRNAs) in the etiology of schizophrenia is increasingly recognized. Microdeletions at chromosome 22q11.2 are recurrent structural variants that impart a high risk for schizophrenia and are found in up to 1% of all patients with schizophrenia. The 22q11.2 deletion region overlaps gene DGCR8, encoding a subunit of the miRNA microprocessor complex. We identified miRNAs overlapped by the 22q11.2 microdeletion and for the first time investigated their predicted target genes, and those implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 85 publications
4
54
0
3
Order By: Relevance
“…Subtle alterations in miRNA expression levels can have profound effects on brain development and plasticity, especially involving synapses 103,104 . Recent studies propose that DGCR8 may play a part in modifying the expression of genes outside of the 22q11.2 deletion region that contribute to the neuropsychiatric and other phenotypes associated with 22q11.2DS 63,72,101,105 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Subtle alterations in miRNA expression levels can have profound effects on brain development and plasticity, especially involving synapses 103,104 . Recent studies propose that DGCR8 may play a part in modifying the expression of genes outside of the 22q11.2 deletion region that contribute to the neuropsychiatric and other phenotypes associated with 22q11.2DS 63,72,101,105 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…In addition to DGCR8 -related changes in miRNAs, the high density of miRNAs in the 22q11.2 deletion region and the accumulative insight into their function indicate that these functional non-coding RNAs may themselves have a role in the variable expression of 22q11.2DS 73,105,106 . These effects on expression are likely to involve not only the central nervous system (CNS) but also the cardiovascular system and other aspects of embryonic development 73,105,106 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…This hypothesis, however, does not account for the variability and similarity of phenotypes in individuals with central and distal deletions who are disomic for DGCR8 . In a study by Merico et al [2014], the authors showed that the miRNAs in 22q11.2 are involved in the regulation of expression of genes in a number of developmental pathways which could be affected by reduced levels of these miRNAs. Using Drosophila melanogaster as a model system, Luhur et al [2014] demonstrated that Pasha is involved in neuronal organization.…”
Section: Variability Of Phenotypementioning
confidence: 99%
“…The nested proximal A-B region contains 6 putative miRNAs and the gene DCGR8 which encodes Pasha, a component of the miRNA processing machinery. The potential role of miRNA in the pathogenesis of deletion phenotypes has been investigated and suggests a role, not only for the miRNAs in the regions themselves but also for the dysregulation of miRNA processing due to the haploinsufficiency of DCGR8 [Brzustowicz and Bassett, 2012;de la Morena et al, 2013;Merico et al, 2014]. Brzustowicz and Bassett [2012] propose that haploinsufficiency of DGCR8 destabilizes developmental pathways by perturbing the miRNA regulatory network.…”
Section: Variability Of Phenotypementioning
confidence: 99%
“…The pathologic mechanisms underlying these findings remain unknown but are deserving of future study. 34,35 Epidemiologic study design in the molecular era…”
Section: Molecular Mechanisms and Fetal Factorsmentioning
confidence: 99%